Forelimb Movement Disorder in Rat Experimental Model - Marešová, D; Kotková, K; Kozler, P; Pokorný, J (Physiological research, 2019)
Study of motor activity is an important part of the experimental models of neural disorders of rats. It is used to study effects of the CNS impairment, however studies on the peripheral nervous system lesions are much less frequent. The aim of the study was to extend the spectrum of experimental models of anterior limb movement disorders in rats by blockade of the right anterior limb brachial plexus with the local anesthetic Marcaine (Ma), or with aqua for injection administered into the same location (Aq) (with control intact group C). Two other groups with anterior limb movement disorders underwent induction of cellular brain edema by water intoxication (MaWI and AqWI). Results showed a lower spontaneous motor activity of animals in all experimental groups versus controls, and lower spontaneous motor activity of animals in the MaWI group compared to other experimental groups in all categories. There was no difference in spontaneous activity between the groups Ma, Aq and AqWI. Our study indicates that alterations of spontaneous motor activity may result from the impaired forelimb motor activity induced by the anesthetic effect of Marcaine, by the volumetric effect of water, as a result of induced brain edema, or due to combination of these individual effects.
Keywords: intoxikace vodou; edém mozku; přední končetina; pohybová aktivita; Movement Disorders; krysa rodu Rattus; Brain Edema; zvířata; potkani Wistar; Rats, Wistar; Male; Water Intoxication; pohybové poruchy; Rats; Motor Activity; Animals; mužské pohlaví; Disease Models, Animal; Forelimb; modely nemocí na zvířatech